A Mathematical Model of Iron Deficiency Anaemia and Its Impact on Cognitive Function in Young Women Aged 18-22 Years - A. Amalarathinam,; Sabarmathi A,; Pooja C., (The Bioscan, 2026)
A mathematical model of iron deficiency anaemia and its impact on cognitive function in young women aged 18-22 years is formulated. The boundedness of the system is verified using Gronwall’s inequality. Equilibrium points are found. The local stability of the model is analysed around the equilibrium points. The global stability of the model is analysed using Lyapunov’s theorem on stability. Numerical simulations are carried out using MATLAB. Keywords Boundedness, Cognitive Function, Equilibrium Analysis, Global Stability, Gronwall’s Inequality, Iron Deficiency Anaemia, Local Stability, Lyapunov’s Theorem.